Expression of hepatic miRNAs targeting porcine glucocorticoid receptor (GR) 3′UTR in the neonatal piglets under a maternal gestational betaine supplementation - Demin Cai; Haoyu Liu; Mengjie Yuan; Shifeng Pan; Yimin Jia; Ruqian Zhao (Data in Brief, 2016)
Glucocorticoid receptor (GR) has been previously demonstrated an important transcriptional factor of hepatic metabolic genes in the neonates under a maternal gestational betaine supplementation (“Gestational dietary betaine supplementation suppresses hepatic expression of lipogenic genes in neonatal piglets through epigenetic and glucocorticoid receptor-dependent mechanisms” Cai et al., 2015 [1]). Here we provide accompanying data about the expression of hepatic miRNAs targeting porcine GR 3′UTR in the neonatal piglets. Liver samples were obtained and RNA was isolated. RNA was polyadenylated by poly (A) polymerase and then dissolved and reverse transcribed using poly (T) adapter. The diluted cDNA were used in each real-time PCR assay. The sequences of all the porcine miRNAs were acquired from miRBase (http://www.mirbase.org/). miRNAs targeting GR were predicted using the PITA algorithm. Among all the predicted miRNAs, 4 miRNAs targeting GR were quantitated by real-time PCR and miRNA-124a, which has been identified to target GR 3′UTR [2,3], was more highly expressed in betaine-exposed neonatal livers. Keywords: miRNAs, GR, Betaine, Neonatal liver